Community Integration of Disability: A Bibliometric and Knowledge-Map Analysis - Wang S; Li D; Liu C; Sun X; Shi Y; Wang H; Zhang H (Journal of Multidisciplinary Healthcare)
Shuaiyou Wang,1 Dingding Li,1 Chenjun Liu,1 Xueting Sun,1 Yage Shi,1 Hongru Wang,2 Huimin Zhang3 1School of Nursing, Xinxiang Medical University, Xinxiang, Henan, People’s Republic of China; 2Nursing of Department, Xinxiang First People’s Hospital, Xinxiang, Henan, People’s Republic of China; 3School of Nursing, Ningxia Medical University, Yinchuan, People’s Republic of ChinaCorrespondence: Huimin Zhang, School of Nursing, Ningxia Medical University, No.1160 Shengli South Street, Xingqing District, Yinchuan, 750001, People’s Republic of China, Email 35290915@qq.comBackground: Community integration (CI) is the ultimate goal of rehabilitation for individuals with disabilities. It plays a significant role in restoring their social functioning and facilitating their reintegration into community and family life. However, no studies have utilized bibliometric methods to explore community integration.Objective: To conduct a review about community integration of disabilities and to clarify the knowledge, hotspots, and trends through the bibliometric method.Methods: Studies on community integration from 1990 to 2023 were retrieved from the Web of Science Core Collection (WOSCC). CiteSpace 6.2.R4 and Microsoft Office Excel 2019 were applied. The CiteSpace node types involved in this study include keyword, reference, cited author, cited Journal, and the dual-map overlay of journals. CiteSpace presented the keyword cluster map, keywords timeline view map, keywords bursts map, and overlay map of journals. Microsoft Office Excel 2019 was used to present the trend of annual publications and draw up related tables and figures.Results: A total of 2239 hits were included. The number of publications related to community integration is increasing gradually. The three most frequent keywords is Brain Injury (571, 13%), Individuals (488, 11%), Quality of Life (434, 10%). Keyword cluster map and timeline map with eight clusters were obtained, and the current strongest citation burst keywords are social participation, substance use, experiences, interventions, and Afghanistan. Willer is the author with the most citations. McColl has the largest centrality in the first ten cited authors. The most cited reference is published by the World Health Organization (WHO). Archives of Physical Medicine and Rehabilitation is the journal with the highest co-citation frequency. The overlay map of journals presented four distinct paths: the journals in “psychology education, health” and “neurology, sports, ophthalmology” often cite journals in “health, nursing, medicine” and “psychology, education, social”.Conclusion: Community integration for individuals with disabilities is gradually becoming a hot topic. Research on community integration related to traumatic brain injury (TBI), stroke, children, and spinal cord injuries is current focus of community integration. Future research should explore the experiences and feelings of different groups of disabilities regarding community integration and develop more effective interventions for their community integration. Community integration is complex, and future research on community integration for individuals with disabilities needs to be explored more specifically.Keywords: community integration, community reintegration, disability, rehabilitation, quality of life, CiteSpace, bibliometric